SEXUAL EDUCATION AND EDUCATION FOR SEXUALITY AIMED AT ADOLESCENTS: A DISCOURSE READING OF SOCIAL EDUCATIONAL PRACTICES ON SEXUALITY IN BASIC EDUCATION IN BRAZIL AND PORTUGAL IN THE LIGHT OF MICHEL FOUCAULT - Souza Monteiro, Solange Aparecida de [UNESP]; Momesso, Maria Regina [UNESP] (Fundacao Univ Tocantins, 2021)
The article presents a theoretical and bibliographical review about the theme of Sexual Education in Brazil and Portugal, highlighting the documents of each country. Reading and writing are understood as social practices. Theoretically and methodologically, the revised documents constitute an empirical corpus of reading and analysis from the french discursive perspective and seeks to carry out an analysis supported by Michel Foucault's theories. In Brazil, documents are prescriptive, designed to guide pedagogical proposals for teachers. These documents operate discourses on rights for childhood and adolescence. But they also regulate and produce an education administered and conducted with the purpose of preparing them for life in society and for productive work. And, in Portugal, the Report - Monitoring and Evaluation of the Implementation of Law No. 60/2009 of 6 August was analyzed, which proposes the mandatory nature of Sexuality Education in schools in Portugal.
Keywords: Education; Social Practices; Sexuality; Adolescence; Brazil; Porugal